Hepatoblastoma of early childhood as an indicator of Gardner’s syndrome - Wojnicka-Stolarz, Małgorzata; Juza, Anna; Staroń, Robert; Lewandowski, Bogumił; Gutkowski, Krzysztof (European Journal of Clinical and Experimental Medicine, 2013)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Familial adenomatous polyposis (FAP) is a genetically determined disease characterized by the presence of multiple colorectal adenomatous polyps (usually more than 100). FAP and its variants are caused by mutations in the tumor suppressor gene (adenomatous polyposis coli - APC), located on chromosome 5q21-q22 and also MUTYH gene mutation. This syndrome accounts for about 1 percent of all colorectal cancers. FAP connected with APC follows an autosomal dominant pattern, MUTYH gene mutation is recessively inherited, but up to 25 percent cases are due to new or de novo gene mutations. Clinical manifestations of FAP are not only a presence of multiple colorectal polyps, but also a number of extracolonic manifestation associations with this disease. We present a case of Gardner’s syndrome being a rare variant of FAP diagnosed in 21-year-old male patient who has been treated due to hepatoblastoma in early childhood.